Pengaruh Variasi Posisi Throttle Terhadap Arus Motor, Konsumsi Baterai, Dan Akselerasi Motor Listrik (Modifikasi Vario 125) - Rohman, Muhammad Fathur; Laksana, Alfian Hudan; Himawan, Citrakara U. S. K. (Journal BEARINGS: Borneo Mechanical Engineering and Science, 2024)
To reduce the use of fuel-powered motorbikes to avoid air pollution, one way is to shift the use of fuel to electrical energy. Currently, the use of electrical energy for transportation has begun to be in demand by the public, because it does not cause noise pollution, low operating costs, and lightweight vehicles. Converting a motorbike into an electric bike will solve this problem. This study uses an experimental method by comparing two settings on the controller from the default condition (Acceleration 0%; Power Limit 80%; Speed Limit 70%) to the maximum condition (Acceleration 30%; Power Limit 100%; Speed Limit 100%), which is then tested on the motor current, battery consumption, and acceleration on the converted motorbike. Based on data analysis and discussion of the study, it can be concluded that changes in the throttle curve settings on the controller can affect the amount of current, the amount of battery consumption, and acceleration on a motorbike that has been converted into an electric bike. Changing the controller settings from default conditions (Acceleration 0%; Power Limit 80%; Speed Limit 70%) to maximum conditions (Acceleration 30%; Power Limit 100%; Speed Limit 100%) is effective in increasing the speed and acceleration of converted electric vehicles. However, changing these settings will increase the current on the motor and battery consumption. In default conditions, the BLDC motor RPM is 3104 RPM (Motor current 31.8 Ampere), after further settings, the BLDC motor RPM increases to 3925 RPM (Motor current 51.4 Ampere)